“I go. I return. I am confused”: Reflections on Armenian Music Ideas in Multi-sited Research - Giovannini, Ortensia (European Journal of Musicology, 2022)
Doing ethnomusicological research about diaspora and music means travelling. Travelling back and forth to Armenian groups in Italy and France and being in the Republic of Armenia to understand and interpret, using the dialogical approach, the musical knowledge of particular individuals of communities and their self-identification as Armenians through music.By sharing and pondering opinions and experiences in different situations, the article discusses ‘Armenianness’ in the music of the protagonists of Milan’s musical practices comparing their discourses with those of other Armenians in Paris and Yerevan. It analyses how perceptions formed in Milan were a conditioning factor at the beginning of the research. It discusses also how the researcher had to adjust her understanding after discovering other musical identities in Armenian groups in France and Armenia and how coming back to Milan with a renewed awareness was pivotal in reflecting the diverse and divergent ways of being Armenian in music.Music can accommodate and direct shifting senses of self. Discovering several Armenian musical identities has revealed a reality where music expresses a will to remember history and at the same time an increasingly multiethnic, globalised Armenian culture, rather than a monolithic musical culture.